2020
DOI: 10.1080/15384101.2020.1783934
|View full text |Cite
|
Sign up to set email alerts
|

miR-203 promotes HaCaT cell overproliferation through targeting LXR-α and PPAR-γ

Abstract: Psoriasis is an immune-mediated chronic inflammatory skin disease. Keratinocyte hyperproliferation has been regarded as a significant event in psoriasis pathogenesis. Considering the vital role of miRNA-mediated mRNA repression in psoriasis pathogenesis, in the present study, we attempted to investigate the mechanism of keratinocyte overproliferation from the point of miRNA-mRNA regulation. Both online microarray expression profiles and experimental results indicated that the expression of LXR-α and PPAR-γ was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
4
16
0
Order By: Relevance
“…Suppressor of cytokine signaling 3 (SOCS-3), the first reported target gene of miR-203, has also been identified to regulate keratinocyte proliferation and differentiation (10). Moreover, a recent study (25) has shown that liver X receptor-α (LXR-α) and peroxisome proliferator-activated receptor-γ (PPAR-γ) are remarkably downregulated in psoriatic lesions, and the overexpression of each gene is sufficient to inhibit keratinocyte proliferation. miR-203 negatively regulates the expression of LXR-α/PPAR-γ by directly targeting 3 ′ UTRs of their mRNAs, suggesting that the miR-203-LXR-α /PPARγ axis is crucially involved in the hyperproliferative phenotype of psoriatic keratinocytes and may provide drug targets for psoriasis treatment.…”
Section: Mir-203mentioning
confidence: 99%
“…Suppressor of cytokine signaling 3 (SOCS-3), the first reported target gene of miR-203, has also been identified to regulate keratinocyte proliferation and differentiation (10). Moreover, a recent study (25) has shown that liver X receptor-α (LXR-α) and peroxisome proliferator-activated receptor-γ (PPAR-γ) are remarkably downregulated in psoriatic lesions, and the overexpression of each gene is sufficient to inhibit keratinocyte proliferation. miR-203 negatively regulates the expression of LXR-α/PPAR-γ by directly targeting 3 ′ UTRs of their mRNAs, suggesting that the miR-203-LXR-α /PPARγ axis is crucially involved in the hyperproliferative phenotype of psoriatic keratinocytes and may provide drug targets for psoriasis treatment.…”
Section: Mir-203mentioning
confidence: 99%
“…Moreover, in vitro experiments showed that miR-203 expression is upregulated after IL-17 stimulation in HaCat cells and that miR-203 is involved in the activation of the JAK2/STAT3 signalling pathway, which contributes to VEGF secretion and the perpetuation of pathological angiogenesis [ 19 ]. Recently, it has been described that miR-203 negatively regulates keratinocyte proliferation through the direct targeting of NR1H3 and PPARG [ 22 ]. Therefore, in psoriasis, the data suggest that miR-203 may be involved in skin epidermal hyperplasia, inflammation and angiogenesis ( Figure 2 ).…”
Section: Role Of Mirnas In the Skin Pathogenesis Of Cutaneous Immumentioning
confidence: 99%
“…Psoriasis, an immune-mediated chronic in ammatory skin disease, is featured with epidermal hyperplasia, angiogenesis, and in ammatory cell in ltration (15,16). It is a key psoriasis treatment to inhibit these cellars events.…”
Section: Discussionmentioning
confidence: 99%